Exploring stakeholder experiences of dietetic service and care delivery: A systematic qualitative review. Issue 1 (29th July 2022) - Elliott, Andrea; Gibson, Simone
Abstract: Background: There is limited understanding of patients' and healthcare professionals' perceptions and experiences of receiving and delivering dietetic care, respectively. This systematic review of the literature used qualitative synthesis to explore the perceptions and experiences of multiple stakeholders involved in the delivery of nutrition care and dietetic service. Methods: MEDLINE, Embase, CINAHL, Cochrane Library, Scopus, ISI Web of Science, PsycINFO and ProQuest were systematically searched. Study characteristics and perceptions of stakeholders regarding nutrition care services were extracted. Qualitative synthesis was employed and thematic analysis conducted. Results: Five themes were identified from 44 studies related to stakeholders' perceptions of dietetic services. Studies included quantitative, qualitative and mixed methods involving patients, families, dietitians and other healthcare professionals. The themes were (1) patients desiring a personalised approach to nutrition care; (2) accessing dietetic service; (3) perceived impact of nutrition care on the patient; (4) relationships between stakeholders; and (5) beliefs about nutrition expertise. Two themes were specific to patients; these were the desire for individualised care and the impact of nutrition care. Within each theme perceptions varied with patients' views often contrasting with those of dietetic service providers. Conclusions: Experiences of dietetic service do not always meet stakeholder expectations which impacts on patient engagement. Seeking stakeholder input is imperative to design dietetic services that engage patients in positive and supportive clinical partnerships. Abstract :   Key points: Stakeholder perceptions of dietetic service and care delivery included themes around a need for a personalised approach to nutrition assessment and intervention, enablers and barriers to accessing dietetic services, the importance of relationships between stakeholders and a range of beliefs about nutrition expertise. Experiences of dietetic services did not always meet stakeholder expectations which impacted on patient engagement. Stakeholder perceptions of dietetic service and care delivery provide valuable insights which can be used to better meet patient, healthcare service and community needs, as well as inform dietetic curricula to prepare graduates for authentic patient‐centred care.